Linking theory with practice in port performance and benchmarking. (1st January 2012) - Bichou, Khalid
This paper reviews the main approaches and techniques for port performance and efficiency, highlights several shortcomings of the contemporary literature on the subject, and emphasises the need to bridge the gap between theory and port practice. By laying the emphasis on the technology variations in port equipment and handling systems, the procedural differences in terminal operations, the network structure of port and terminal systems, and the interplay between controllable and uncontrollable factors, we demonstrate why such aspects must be taken into account when conducting empirical studies on port benchmarking and efficiency. In this paper, we review the literature on port performance and point out its shortcomings with a view to link theory with port practice. The focus of the discussion is on the potential distortions stemming from both the limitations of the selected methodology and the difficulty to incorporate port practice into performance benchmarking models